Clinical Characteristics and Outcome of Severe Acute Respiratory Syndrome Coronavirus 2 Infection in Italian Pediatric Oncology Patients: A Study From the Infectious Diseases Working Group of the Associazione Italiana di Oncologia e Ematologia Pediatrica. (11th July 2020) - Bisogno, Gianni; Provenzi, Massimo; Zama, Daniele; Tondo, Annalisa; Meazza, Cristina; Colombini, Antonella; Galaverna, Federica; Compagno, Francesca; Carraro, Francesca; De Santis, Raffaela; Meneghello, Linda; Baretta, Valentina; et al.
Abstract: Background: Little is known as yet about the outcome of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children being treated for cancer. Methods: We collected information on the clinical characteristics and outcomes of a cohort of 29 children (16 female and 13 male; median age, 7 years [range, 0–16 years]) diagnosed with SARS-CoV-2 infection while on chemotherapy/immunotherapy (n = 26), or after stem cell transplantation (n = 3) during the peak of the epidemic in Italy. These patients suffered from leukemia (n = 16), lymphoma (n = 3), solid tumors (n = 10), and Langerhans cell histiocytosis (n = 1). Results: The course of the disease was mild in all cases, with only 12 children developing symptoms (pneumonia in 3 cases), and none needing intensive care. Fifteen patients were hospitalized, including 7 asymptomatic patients. Nine patients (including 5 with no symptoms) were given hydroxychloroquine, and 3 of them were also given lopinavir/ritonavir. Among the 26 patients on chemotherapy/immunotherapy, the treatment was suspended in 16 cases for a median of 26 days (range, 15–68 days), whereas 8 patients continued their chemotherapy and 2 had minor modifications to their treatment regimen. Conclusions: SARS-CoV-2 infection seems to take a milder clinical course in children than in adults with cancer. Specific SARS-CoV-2 treatment seems unnecessary for most children. In light of our findings, and albeit with the necessary caution, we suggest avoiding major changes to planned anticancer treatments in pediatric patients acquiring COVID-19. Abstract : We describe clinical characteristics and outcomes of 29 SARS-CoV-2–infected children with cancer. In comparison to adult oncology patients, children presented a milder clinical course. A substantial number of them continued their anticancer treatment without major modifications.